A coursebook on scientific and professional writing for speech-language pathology - Hegde, M. N. (Mahabalagiri N.), 1941- (San Diego, CA : Plural Publishing, Inc., 2024)
"A Coursebook on Scientific and Professional Writing for Speech-Language Pathology, Sixth Edition is a unique interactive resource to help students develop the strong writing skills necessary for a successful clinical or academic career in speech-language pathology. The book not only describes the principles of good writing, but also contains numerous opportunities to practice writing skills replete with exemplars. The Coursebook is ideal for dedicated courses on scientific and/or professional writing, and can also be used in courses on assessment, research methods, and clinical methods and practicum"--
Includes bibliographical references and index.
Keywords: Speech therapy -- Authorship; Medical writing